2016
DOI: 10.1007/s13364-016-0285-x
|View full text |Cite
|
Sign up to set email alerts
|

Activity pattern and fat accumulation strategy of the Natterer’s bat (Vespertilionidae, Chiroptera) swarming population indicate the exact time of male mating effort

Abstract: Studies concerning bat autumn swarming behavior suggest that the main purpose of this phenomenon is mating. However, the process of fat accumulation is crucial for surviving winter, and it seems to be in clear conflict with a need to strive for the opportunity to mate prior to hibernation. Investment in one activity limits the other one creating a trade-off between them. The aim of our study was to describe the activity pattern of each sex-age group (adult males, adult females, subadults) of the Natterer's bat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The monthly NAO indicated that in 2010 the December was particularly harsh. At this time of the winter, Natterer's bats are typically still active as indicated by a lot of activity at the hibernaculum according to the logger data (own unpublished data), and especially males try to accumulate their fat reserves very late in Natterer's bats (Kohyt, Rozik, Kozakiewicz, Pereswiet‐Soltan, & Gubała, ). In contrast, Daubenton's bats start to hibernate much earlier (own unpublished data) and thus should not have been affected by the cold conditions during that month.…”
Section: Discussionmentioning
confidence: 99%
“…The monthly NAO indicated that in 2010 the December was particularly harsh. At this time of the winter, Natterer's bats are typically still active as indicated by a lot of activity at the hibernaculum according to the logger data (own unpublished data), and especially males try to accumulate their fat reserves very late in Natterer's bats (Kohyt, Rozik, Kozakiewicz, Pereswiet‐Soltan, & Gubała, ). In contrast, Daubenton's bats start to hibernate much earlier (own unpublished data) and thus should not have been affected by the cold conditions during that month.…”
Section: Discussionmentioning
confidence: 99%
“…Autumn swarming is accompanied by intense social vocalizations that are associated primarily with mating [14, 25]. In most swarming bat species, males outnumber females at autumn swarming sites [14, 24, 26, 27]. Genetic studies revealed that autumn swarming increases genetic diversity within populations, which is especially important for highly philopatric bat species [26, 28, 29].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, despite the temporal separation between spermatogenesis and mating that is possible in the reproductive cycle of temperate bats due to prolonged sperm storage 5,10 it seems likely that a selective advantage does exist for males to be ready to mate soon after females have completed lactation. Mating within day roosts in the summer habitat 16 , and peak autumn swarming activities [25][26][27][28] , both occur within a short period that is post-maternity and pre-hibernation for our two study species. The timing of mating readiness in males and receptivity in females differs between these sympatric congeners but is highly synchronised within each species.…”
Section: Discussionmentioning
confidence: 92%
“…Mating at swarming sites may maximise their breeding potential through copulation with numerous sexual partners and outbreeding with non-related females from different colonies drawn from a large catchment area 16 . In contrast, M. nattereri adult males typically commence spermatogenesis during July and August then leave their summer habitat (presumably to migrate to autumn swarming sites [23][24][25] during September. These observations fit well with the temporal distribution of swarming activity recorded in these species, with the peak in M. daubentonii activity at swarming sites occurring during August, and the peak in M. nattereri activity at swarming sites occurring during September [25][26][27][28] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation